Вплив ефективності елементів ядерного енергоблоку з гелієвою газовою турбіною на ККД установки в комбінованому режимі роботи - Доник, Т .В.; Сафронова, О. О.; Філатов, А. А. (Енергетика і автоматика, 2017)
The influence of elements of nuclear power with a helium gas turbine on efficiency the installation in a combined mode T. Donyk, O. Safronova, A. Philatov In a continuous rise in prices for fuel resources and reduce their stocks one way to solve the energy problems of mankind is the active development of nuclear energy. Instead of working in many countries the reactors of second and third generation are developing fourth generation, characterized by increased performance efficiency and safety. The concept of high-temperature reactor hazooholodzhuvalnoho formed the basis of the international project "Gas Turbine - Modular Helium Reactor" in which to convert the thermal energy of the heated helium into mechanical work and then into electricity using gas turbine. The purpose of research - analysis of the thermodynamic cycle unit with a modular nuclear reactor thermal capacity of 250 MW in combined mode power generation and district heating, efficiency impact assessment install elements of its electrical efficiency and size of electric and thermal power. Materials and methods of research. Power plant GT-mGy thermal capacity of 250 MW consists of two connected blocks, modular helium reactor power conversion and power - turbine installation. Power conversion unit, in turn, consists of compressors, low and high pressure gas turbine, located on one shaft compressors regenerator, preliminary and intermediate heat exchangers and the generator driven by the turbine. This setting is complicated by a closed Brayton cycle with regeneration and intercooling heat in the compressor, as the working fluid used helium. Power conversion unit can operate in two modes - basic mode power generation and combined, which includes power generation and use of waste heat for district heating. Work installation in combined mode differs from the basic fact that the heat is discharged cooling fluid, not given to cooling towers in air, and is utilized for district heating purposes. The value of thermal power generated in combined mode of installation depends on the absolute values of power and previous intermediate heat coefficients and their effectiveness. For the study the efficiency of the unit with the parameters below the settlement, the main parameters affecting simultaneously on all three investigated values were set to efficiency turbines and compressors of high and low pressure. Results. This work used a complex mathematical model cycle gas turbine that includes a serial calculation parameters for combined cycle mode of the unit with a thermal capacity of 250 MW. Established that the thermal reactor power of 250 MW in combined mode is useful electrical power is 69.66 MW installation at an electrical efficiency - 27.7 %. Thermal power coming to the needs of the consumer, was 182.13 MW. Necessary capacity heat exchange equipment are: regenerator - 123.7 MW; preliminary heat exchanger - 132.74 MW; intermediate heat exchanger - 65.99 MW. For the low-pressure compressor efficiency while reducing design value of 0.875 to 0.75 technically attainable normally allows reducing electric power unit efficiency by 3.5 %. The electric power thus reduced to 4 MW and heat increased from 182.13 to 185.3 MW. The effectiveness of low-pressure compressor for the calculation results have a greater impact on the efficiency of electric power and cycle efficiency than high-pressure compressor. Reducing the efficiency of the design value of 0.85 to 0.75 reduces the efficiency of the installation and the electrical power by 2% and 3 MW respectively, and heat output while increasing to 186.5 MW. By reducing the turbine efficiency of the estimated value of 0.93 to 0.75 reduces the electrical efficiency of the unit by 8% drop in electrical power to 21 MW and increase the heat to 16 MW. Conclusions 1. The calculation of the thermodynamic cycle modular unit with a heat output of 250 MW reactor at the combined mode of power generation and district heating have shown that useful electric power unit is 69.66 MW electrical efficiency - 27.7% of useful heat output - 182 13 MW. 2. The main influence on the efficiency of turbine cycle provides. Reducing the turbine efficiency of the estimated value of 0.93 to 0.75 leads to a decrease in the efficiency of the electric power unit 8% drop in electrical power to 21 MW and increase the heat to 16 MW. 3. Reduction efficiency compressor, low pressure strongly affects the electrical efficiency and electrical output than reducing the effectiveness of high pressure compressor. For the value of useful heat output there is an inverse relationship.